The molecular properties of the bHLH TCF4 protein as an intrinsically disordered hub transcription factor - Nikola Sozańska; Barbara P. Klepka; Anna Niedzwiecka; Lilia Zhukova; Michał Dadlez; Beata Greb-Markiewicz; Andrzej Ożyhar; Aneta Tarczewska (Cell Communication and Signaling)
Abstract Background Transcription factor 4 (TCF4) is a member of the basic helix-loop-helix (bHLH) family of transcription factors that guides proper embryogenesis, particularly neurogenesis, myogenesis, heart development and hematopoiesis. The interaction of TCF4 with DNA is dependent on the presence of a conserved bHLH domain, particularly the presence of a basic (b) motif. Most mutations in the Tcf4 gene are either associated with the development of serious nervous system disorders, such as Pitt-Hopkins syndrome or schizophrenia, or are lethal. Although TCF4 is essential for the proper development and function of the human body, there is a lack of fundamental knowledge about the structure of TCF4 since structural studies were previously limited exclusively to its bHLH. Methods Recombinant full-length TCF4 was expressed in bacterial cells and purified using chromatographic techniques. To compare the properties of TCF4 in its apo and holo form, we determined the dissociation constant (KD) of the TCF4:DNA complex using independent methods, including fluorescence polarization (FP), electrophoretic mobility shift assay (EMSA), and fluorescence correlation spectroscopy (FCS). Then we compared the properties of TCF4 in its apo and holo form in relation to the changes of the conformation of the polypeptide chain (hydrogen/deuterium exchange mass spectrometry; HDX-MS), hydrodynamic properties (e.g., sedimentation-velocity analytical ultracentrifugation; SV-AUC), and stability (thermal shift, circular dichroism; CD). Results We demonstrate the molecular characteristics of TCF4, the dimer of which is one of the largest intrinsically disordered proteins (IDPs) described to date. According to our findings, the structure of TCF4 is extensively disordered. Only the bHLH domain exhibits a stable fold. Strikingly, Ephrussi-box (E-box) binding via the bHLH domain has no significant effect on the disordered nature of TCF4, but it does influence the dynamic of bHLH and stability of the protein. Conclusions We suggest that bHLH plays the role of an anchor localizing TCF4 to specific gene sequences. The dual nature of the TCF4 structure and the fact that the intrinsically disordered regions (IDRs) represent most of the protein sequence, suggest that TCF4 may act as a hub transcription factor regulating the expression of specific genes through the interaction of IDRs with gene-specific partners.